Injury incidence and injury patterns in professional football: the UEFA injury study - Ekstrand, J.; Hägglund, M.; Walden, M. (British Journal of Sports Medicine, 2011)
Objective To study the injury characteristics in professional football and to follow the variation of injury incidence during a match, during a season and over consecutive seasons.